Construction of nano-scale cellular environments by coating a multilayer nanofilm on the surface of human induced pluripotent stem cells. Issue 28 (10th July 2019) - Han, Uiyoung; Kim, Yu Jin; Kim, Wijin; Park, Ju Hyun; Hong, Jinkee
Abstract : We established a method to fabricate a functional cellular nano-environment of induced pluripotent stem cells by a multi-layered nanofilm coating on the cell membrane. Abstract : Interactions with peripheral environments, such as extracellular matrix (ECM) and other cells, and their balance play a crucial role in the maintenance of pluripotency and self-renewal of human pluripotent stem cells. In this study, we focused on a nano-sized artificial cellular environment that is directly attached to the cytoplasmic membrane as a facile method that can effect intercellular interactions at the single-cell level. We designed multilayered nanofilms that are self-assembled on the surface of human induced pluripotent stem cells (iPSCs), by repetitive adsorption of fibronectin and heparin or chondroitin sulfate. However, the surface modification process could also lead to the loss of cell–cell adhesion, which may result in apoptotic cell death. We investigated the proliferation and pluripotency of the iPSCs coated with the nanofilm in order to establish the suitable nanofilm structure and coating conditions. As a result, the cell viability reduced with the increase in the duration of the coating process, but the undifferentiated state and proliferation of the cells were maintained until 2 bilayers were coated. To suppress the dissociation-induced apoptosis, Y-27632, the Rho-associated kinase inhibitor (ROCKi), was added to the coating solution; this allowed the coating of up to 4 bilayers of the nanofilm onto the iPSCs. These results are expected to accelerate the pace of iPSC studies on 3-dimensional cultures and naïve pluripotency, in which the regulation of cellular interactions plays a critical role.